YOUNG CHILDREN’S FREEDOM OF CHOICE IN CHILD-CENTRED EDUCATIONAL PRACTICE - Ozola, Aija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The importance of young children’s freedom of choice has been discussed since Froebel’s and Montessori’s contribution to the pedagogical ideas related to early childhood education. However, the theoretical framework of the term and its contents in modern early childhood education does not offer detailed description and would rather be characterized as incomplete and fragmented. The current study is an attempt to partly fill the gap between educational theory and practice basing on early childhood teachers’ empirical experience and beliefs on children’s freedom of choice.The aim of the study is to identify early childhood teachers’ beliefs on children’s freedom of choice in child-centred educational practice. Focus group discussions were conducted with early childhood teachers implementing early childhood curriculum in municipal early childhood education institutions located in Riga, the capital city of Latvia. Data were analysed using the method of qualitative content analysis. The findings revealed very positive attitude of teachers towards children’s freedom of choice and existence of teachers’ personal meaning of the term and its contents. The benefits and possible risks of implementing children’s freedom of choice were identified as well as factors enabling and hindering its implementation.